Anti-cropping digital image watermarking using Sudoku. (1st January 2013) - Khalid, Shamsul Kamal Ahmad; Deris, Mustafa Mat; Mohamad, Kamaruddin Malik
Many digital image watermarking schemes have been developed to embed copyright information into an image. However, an attacker may reuse parts of a watermarked image by cropping out unwanted parts. Several techniques have been designed to overcome this attack but due to their limited redundancy approach, some section of the images can still be retrieved without detectable watermark. In this paper, a new watermarking scheme that is robust against severe cropping using Sudoku is proposed. It is based on Sudoku's permutation property that allows evenly distributed copies of watermark pieces in all parts of the cover image. A valid Sudoku solution is used during the embedding as well as during the detection of the watermark. Using classic 9 × 9 Sudoku, the scheme demonstrated robustness of up to 94% of random cropping.